Analisis Implementasi E-Puskesmas di Puskesmas Terara Lombok Timur - Arsyam, Haeril; Sulaiman, Lalu; Setiawan, Sabar (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACTThe digitalization of healthcare services through e-Puskesmas aims to enhance administrative efficiency and patient data integration in community health centers (puskesmas). Puskesmas Terara, East Lombok, has implemented this system; however, its effectiveness still faces various technical and non-technical challenges that require further analysis. This study employs a qualitative approach using in-depth interviews and focus group discussions (FGD). The research informants include medical personnel, administrative staff, service unit coordinators, the IT team, and puskesmas management. The implementation of e-Puskesmas has provided significant benefits, such as efficient data recording, integration between service units, and clearer service information. However, several technical challenges were identified, including network disruptions and system instability. Additionally, non-technical obstacles include a lack of comprehensive training and difficulties in technology adaptation among some staff members. Although e-Puskesmas has improved service effectiveness, system optimization is still necessary. The key recommendations of this study include infrastructure enhancement, the provision of comprehensive technical training, periodic evaluation of application features, and the addition of human resources to the IT team to ensure system sustainability. Keywords: E-Puskesmas, Implementation Effectiveness, Healthcare Services, Technical Challenges, System Development.  ABSTRAK Digitalisasi layanan kesehatan melalui e-Puskesmas bertujuan meningkatkan efisiensi administrasi dan integrasi data pasien di puskesmas. Puskesmas Terara, Lombok Timur, telah mengimplementasikan sistem ini, namun efektivitasnya masih menghadapi berbagai kendala teknis dan nonteknis yang perlu dianalisis lebih lanjut. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara mendalam dan diskusi kelompok terfokus (FGD). Informan penelitian mencakup tenaga medis, staf administrasi, koordinator unit layanan, tim IT, dan manajemen puskesmas. Implementasi e-Puskesmas memberikan manfaat signifikan, seperti efisiensi pencatatan data, integrasi antarunit layanan, dan kejelasan informasi pelayanan. Namun, beberapa kendala teknis ditemukan, seperti gangguan jaringan dan ketidakstabilan sistem. Selain itu, hambatan nonteknis meliputi kurangnya pelatihan mendalam serta kesulitan adaptasi teknologi oleh sebagian staf. Meskipun e-Puskesmas telah meningkatkan efektivitas layanan, optimalisasi sistem masih diperlukan. Rekomendasi utama penelitian ini adalah peningkatan infrastruktur, penyediaan pelatihan teknis komprehensif, evaluasi berkala fitur aplikasi, serta penambahan sumber daya manusia di tim IT guna memastikan keberlanjutan sistem. Kata Kunci: E-Puskesmas, Efektivitas Implementasi, Pelayanan Kesehatan, Kendala Teknis, Pengembangan Sistem.